Manajemen Laba dan Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indoensia) - Indra Kusuma, I Gusti Bagus; Mertha, I Made (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p14, 2021)
The purpose of this study is to determine the effect of earnings management with income increasing and income decreasing patterns on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The population of this research are 167 companies. A total of 105 samples are selected using a purposive sampling technique. Total observations over the 5 years to 525 observations, then divided into two groups, 472 observations for increasing income management and 53 observations for decreasing earnings management. This study uses a simple linear regression analysis technique. The test results show that income increasing earnings management variable does not affect the value of the company, while earnings decreasing earnings management has a negative effect on firm value. Keywords: Firm Value; Earnings Management; Income Increasing; Income Decreasing.